Thermally-Induced Actuations of Stimuli-Responsive, Bicompartmental Nanofibers for Decoupled Drug Release - Jung, Chan Woo; Lee, Jae Sang; Jalani, Ghulam; Hwang, Eun Young; Lim, Dong Woo (Frontiers in Chemistry, 2019)
Stimuli-responsive, anisotropic micro- and nano-structures with different physicochemical properties at discrete compartments have been developed as advanced materials for drug delivery systems, tissue engineering, regenerative medicine and biosensing applications. Moreover, their stimuli-triggered actuations would be of great interest for introduction of functionality of drug delivery reservoirs and tissue engineering scaffolds. In this study, stimuli-responsive, bicompartmental nanofibers (BCNFs) with completely different polymer compositions were prepared through electrohydrodynamic (EHD) co-jetting with side by side needle geometry. One compartment with thermo-responsiveness is composed of methacrylated poly(N-isopropylacrylamide-co-allylamine hydrochloride), poly(NIPAM-co-AAh) while the counter compartment is made up of poly(ethylene glycol) dimethacrylates (PEGDMA). Both methacrylated poly(NIPAM-co-AAh) and PEGDMA at distinct compartments were chemically-crosslinked in a solid phase by UV irradiation, and swollen under aqueous conditions because of hydrophilicity of both poly(NIPAM-co-AAh) and PEGDMA. As temperature increased, BCNFs maintained clear interface between compartments, and showed thermally-induced actuation at nanoscale due to the collapsed poly(NIPAM-co-AAh) compartment under the identical dimension of PEGDMA compartment. Different model drugs, bovine serum albumin and dexamethasone phosphate alternately loaded into each compartment were released at different rates depending on temperature and molecular weight of drugs. These BCNFs as intelligent nanomaterials have great potential for functional tissue engineering scaffolds, and multi-drug delivery reservoirs with stimuli-triggered actuation and decoupled drug release.